2013
DOI: 10.3928/01913913-20130730-03
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Results of Consecutive Exotropia

Abstract: If the choice of surgical planning is based on medial rectus function and the amount of exodeviation, satisfactory alignment would be achieved in the majority of patients with consecutive exotropia. The preoperative amount of exodeviation was the only risk factor of surgical failure in the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 15 publications
5
25
0
Order By: Relevance
“…1,7,8,10–13 We are not aware of any previous studies that have evaluated associations with excessive exodrift per se, but some have evaluated associations with exodeviation recurrence. Two studies found associations between larger preoperative angle of deviation 9,14 and recurrent exodeviation, paralleling our finding of larger preoperative deviation associated with excessive exodrift. Other factors reported as associated with exodeviation recurrence in consecutive exotropia are millimeters of medial rectus advancement 15 and limitation of adduction preoperatively, 11 but these were not found associated with excessive exodrift in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…1,7,8,10–13 We are not aware of any previous studies that have evaluated associations with excessive exodrift per se, but some have evaluated associations with exodeviation recurrence. Two studies found associations between larger preoperative angle of deviation 9,14 and recurrent exodeviation, paralleling our finding of larger preoperative deviation associated with excessive exodrift. Other factors reported as associated with exodeviation recurrence in consecutive exotropia are millimeters of medial rectus advancement 15 and limitation of adduction preoperatively, 11 but these were not found associated with excessive exodrift in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…5,6 Across previous studies the reported magnitude of exodrift ranges from approximately 4 Δ to 7 Δ 6–9 in the early postoperative period, similar to our finding of 4 Δ over 6 weeks. Nevertheless, reporting averages can obscure individual responses.…”
Section: Discussionsupporting
confidence: 88%
“…Mohan et al 17 reported 91% success in a follow-up period of less than 2 years, but noted that this rate decreased to 52% when the follow-up period was longer than 2 years. Additionally, Rajavi et al 18 reported that esotropia etiology did not show any relationship with the success or failure of CXT surgery. In previous studies, controversial results were obtained from various surgical methods, including combined procedures in the treatment of CXT.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of consecutive exotropia varies based on viewpoint: either reversal of previous esotropia surgery, [ 10 ] which involve medial rectus (MR) advancement or cooper's dictum [ 11 ] which involve lateral rectus (LR) recession of unoperated or previously resected muscles, or a combination of the above. [ 1 , 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to predict the outcomes of a secondary operation but there is no standardized procedure with only a few studies comparing different surgeries with small series and short-term follow-up. [ 12 , 16 ] In this study, we evaluated the surgical outcomes of MR advancement and LR recession in postoperative consecutive exotropia with single-stage adjustable suture surgery.…”
Section: Introductionmentioning
confidence: 99%